2015
DOI: 10.2117/psysoc.2015.84
|View full text |Cite
|
Sign up to set email alerts
|

Further Exploring the Relation Between Uncertainty and Attraction

Abstract: This research explored competing predictions for the relation between uncertainty and interpersonal attraction. Two studies investigated whether uncertainty regarding another person's interest is associated with an increase or decrease in attraction. Study 1 revealed that when participants evaluated people whose expressed attraction was either certain or uncertain, participants experienced more liking for those who were associated with certainty. In Study 2, compared to a control condition, uncertainty produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A methodological limitation imposed by these current studies also comes from the continuous scales participants used to report attraction toward targets. These perceptual scales could have been tantamount to indicating ideal mate preferences instead of assessing actual mating decisions or behaviors (see Eastwick, Luchies, Finkel, & Hunt, 2014; Montoya, Faiella, Lynch, Thomas, & DeLuca, 2015). Ipsative scales may have better assessed utilitarians’ STM desirability with participants having to make the trade-off between utilitarian and deontologist in LTM and STM contexts (Jonason, Luevano, & Adams, 2012; Lyons, Marcinkowska, Helle, & McGrath, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A methodological limitation imposed by these current studies also comes from the continuous scales participants used to report attraction toward targets. These perceptual scales could have been tantamount to indicating ideal mate preferences instead of assessing actual mating decisions or behaviors (see Eastwick, Luchies, Finkel, & Hunt, 2014; Montoya, Faiella, Lynch, Thomas, & DeLuca, 2015). Ipsative scales may have better assessed utilitarians’ STM desirability with participants having to make the trade-off between utilitarian and deontologist in LTM and STM contexts (Jonason, Luevano, & Adams, 2012; Lyons, Marcinkowska, Helle, & McGrath, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This signal of trustworthiness could implicate outraged targets as capable of the fidelity necessary for successful LTM. Further, because of the importance of trust in facilitating the approach of prospective mates (Montoya, Faiella, Lynch, Thomas, & DeLuca, 2015;Montoya & Insko, 2008), we further predicted that the basis for the attraction to outraged behavioral repertoires would be rooted in outraged individuals' trustworthiness in relationships.…”
Section: Studymentioning
confidence: 99%
“…In one series of experimental studies, for instance, women reported the greatest attraction to profiles of men when they were uncertain of whether the man liked them “an average” or “above average” amount, compared to when they were certain that man liked them an “above average” amount (Whitchurch et al., 2011). However, in a subsequent investigation, this effect did not fully replicate, as attraction did not significantly differ between the certain liking and uncertain conditions; furthermore, when a within‐subject design was employed, participants became more attracted to the profiles when they gained certainty that the individual liked them (Montoya et al., 2015). These conflicting results may be due to the relatively small sample sizes of both of these studies (47 and 78 participants, respectively).…”
Section: What Is the Source Of Romantic Passion? A Review Of Four Theories/modelsmentioning
confidence: 99%